Molassed dried sugar beet pulp for feeding broiler rabbits - ΚΟΛΑΓΓΗΣ, Σ.; ΞΙΟΥΦΗΣ, Α. (Journal of the Hellenic Veterinary Medical Society, 2019)
Four pelleted rations inclunding 0, 10, 15 and 20% molassed dried sugar beet pulp were used to investigate the posiblity of using this stuff for feeding broiler rabits. There were used 32 white New Zealand rabbits in a 2X4 factorial design. Between rations were not fount statistically significant differences in feed conversion ratio (FCR) during the summer season. On the contrary during winter, the Tukey test shwed that FCR was statistically significanly better for the ration with 20% mollassed dried sugar beet pulp than that without (P<0.05). As a consequence of this during winter was a redution of 12,15% of the cost of feeding to produce one Kg live weight on the ration with 20% molassed dried sugar beet pulp. Therere, the use of molassed ried sugar beet pulp should be recommended to be included in rations for rabbits, particularly for farms which are deprived of climatisation systems during winter.